PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS CANVA DENGAN PENDEKATAN PROBLEM BASED LEARNING PADA MATERI BANGUN RUANG KELAS V SD - Abellia, Julika; Jayanti; Ida Suryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop interactive learning media based on canva with a problembased learning approach on valid, practical and effective fifth grade elementary school spatial construction material. This study uses the R&D (Research and Development) method or development research, in this study the model used is ADDIE which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The subjects in this study were fifth grade students of Elementary School 205 Palembang. Data collection techniques used were interviews, questionnaires and documentation. Data analysis techniques used were validity analysis, practicality analysis and effectiveness analysis. This validation analysis process was validated by three experts, namely media experts, material experts and language experts with an average of 83% categorized as valid. The practicality analysis process with the results of the teacher questionnaire and testing on students at the individual test stage (one to one) using 6 students, and the small group trial stage (small group) using 8 students, after being tested, an average score of 89% was categorized as very practical. The effectiveness analysis process with the results of the student quiz scores getting an average score of 87.31%. Thus it can be concluded that interactive learning media based on canva with a problem-based learning approach on the material of spatial figures of grade V SD is categorized as valid, practical and effective.